INOVASI DAN PEMBANGUNAN DESA DI KABUPATEN GUNUNGKIDUL: INKLUSIVITAS KESEJAHTEERAAN DAN KESETARAAN GENDER - Kartiwi Kartiwi; Andi Pitono; Arwanto Arwanto; Adfin Rochmad Baidhowah (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2022)
Nglanggeran Village, Gunungkidul Regency has high natural tourism potential which is driven by the innovation ability of its citizens in managing this potential. This study aims to analyze how the political aspect in Nglanggeran Village, Gunungkidul Regency is framing innovation in the tourism sector and how innovation in tourism in Nglanggeran Village, Gunungkidul Regency is able to encourage inclusiveness of welfare and gender equality. To do this, this research uses qualitative methods by conducting interviews and quantitative methods by conducting perception surveys to stakeholders. The results of this study indicate that development and innovation have been carried out by Nglanggeran village which have an impact on improving the welfare of the villagers. The initiation of this innovation comes from the ideas and ideas of community members. However, in its execution there is the participation of various stakeholders. Innovation in Nglanggeran village has a positive impact on people's income, especially for those whose livelihoods are related to tourism management and their MSMEs. However, for residents who do not work in this field, they still feel the benefits, one of which is the improvement of facilities or access to their village. In addition, female residents have the same opportunity to provide their views and opinions in the formulation of the tourism village activity program. In addition, capacity building for women is also well implemented. Keywords: Development and Village Innovation, Prosperity, Gender Equality